Pertumbuhan bobot badan ayam hasil persilangan ayam Kampung dengan ayam Bangkok - Wa Ode Rowiyanti; Junaedi; Suparman (Jurnal Sains dan Teknologi Peternakan, 2021)
Efforts that can be made to improve the performance of native chickens are by crossing them with Bangkok chickens. This study aims to determine the growth of body weight from cross-breeding between Kampung chicken and Bangkok chicken. As many as 30 male chicks from a cross between Kampung and Bangkok chickens were used in this study. The crosses used are rooster chicks. The weight of DOC chickens from Bangkok male and Kampung female was 35.22 ± 0.96 grams. There was a significant increase in growth in chickens from crosses between Kampung male and Bangkok female starting at the age of 5 weeks to 8 weeks of age, reaching a body weight of 729.39±39.10 grams. The conclusion of this study was that the growth of Kampung male crossed with Bangkok female can increase the body weight growth of their offspring. A significant increase in performance in crosses between Kampung and Bangkok chickens occurred from 5 weeks of age to 8 weeks of age.